Effect of hybrid (micro- and nano-) fillers on impact response of GFRP composite. (15th December 2015) - Koricho, Ermias G.; Khomenko, Anton; Haq, Mahmoodul; Drzal, Lawrence T.; Belingardi, Giovanni; Martorana, Brunetto
Abstract: The impact behavior of hybrid nano-/micro-modified composite was investigated in Glass Fiber Reinforced Plastics (GFRP). The hybrid nano-/micro fillers chosen were Cloisite® 30B nanoclay and 3M™ Glass Bubbles iM16K. Impact testing at varying energy levels was performed using drop weight impact tests (DWIT). The impact response was evaluated in terms of damage progression by visual observations, evolution of the peak force and stiffness with corresponding absorbed energy. At high impact energy levels, pristine and Glass Bubble modified laminates showed the highest peak force and low absorbed energy with penetration of the impactor through their thickness, while nanoclay-modified laminate showed the highest absorbed energy and minimum peak reaction force without penetration. The hybrid laminate exhibited intermediate absorbed energy and peak reaction force sustained for longer time. Overall, the work demonstrated the ability to tailor composite properties for enhancement of impact performance by using various types, concentrations and configuration of nano/micro particles.